The Behaviour of Consuming Food in Local-level Sportsman - Paudyal, Tika Ram; Sharma, Yam Prasad; Paudel, Yubraj (Butwal Campus Journal, 2024)
The main purpose of this study was to find out the food-consuming practice of local-level sportsmen in Butwal-12, Rupandehi, Nepal. A descriptive and quantitative research design was used in this research. The respondents who lived in Butwal 12 were the population of this study. The interview schedule was the data collection tool. From the total population, 50 local level sportsmen were selected as the sample size for the study. All the local level sportsmen were included using the census sampling technique. After collecting the data, SPSS version 20 was used for tabulation as well as statistical analysis of the raw data, obtaining tables and percentages of related information. The overall study found that local-level sportsmen had poor knowledge of food-consuming practices and the right consumer behaviour for consumer health, which is also regrettable in Butwal Sub-metropolitan City, Rupandehi.